Kıbrıs Sorunun Kral Halid Bin Abdülaziz Döneminde Türk-Suud İlişkilerine Yansıması 1975-1982 - Eş-şemr, Abdullah Bin Hacis; Bostancı, Mustafa (Fırat University, 2016)
Bu araştırma, Kral Halid Döneminde Kıbrıs meselesinin TürkSuud ilişkilerine yansımasını ele almakta ve Suudi Arabistan’ın resmen, maddi, manevi, siyasi yönlerden yardımıyla ilgili tutumunu, İslâmî dayanışma açısından Kıbrıslı Türkler meselesine nasıl baktığını ortaya koymaktadır. Buna ilaveten Suud Hükümeti’nin, Suudi Yatırım Fonu, İslâm Kalkınma Bankası, İslâm Konferansı Örgütü, Dünya İslâm Birliği Rabıta , BM gibi çeşitli vasıtalarla Kıbrıslı Türklere nasıl yardım ettiğini incelemektedir. İki toplumu içine alan tarafsız, hükümran, müstakil, federal bir Kıbrıs devletinin kuruluşuna çağrıda bulunduğu Kıbrıs meselesiyle ilgili İslâm Konferansı Örgütü’nden çıkan kararlarda ve daha birçok hususlarda konuya nasıl katkıda bulunduğunu açıklamaya çalışmaktadır. Ve yine Suudi Hükümeti’nin, İslâm Konferansı Örgütü’nde gözlemci konumunda bulunmaları için Kıbrıslı Türlere nasıl doğrudan ve tam destek verdiğini, Kıbrıslı Türklerin davasına destek veren az sayıda İslâm devletinden biri olduğunu anlatmaktadır. Araştırma, Kral Halid döneminde Kuzey Kıbrıs’taki Türk toplumuna yapılan yardım çalışmalarının Türk-Suud ilişkilerine yansımaları özetlenerek son bulmaktadır. Dışişleri Bakanları Konferansı’na ev sahipliği yapmıştır. Böylece Türkiye’nin Arap ve İslâm devletleriyle ilişkilerinde yeni bir dönem başlamıştır

The present Study handles and tacles reflection of the Cyprus Issue onto Turkish-Saudi relations in the period of King Khalid and reveals attitude of Saudi Arabia related with its assistance in terms of official, material, moral, political aspects, how the Saudi Arabia looks at the issue of Turkish Cypriots in view of the Islamic solidarity. Furthermore, this study examines how Saudi Arabia helped to the Turkish Cypriots by various means such as the Saudi Government's Saudi Investment Fund, Islamıc Development Bank, Organization of Islamic Conference, World Islamic Union Rabıta , UN, etc. In the Resolutions issued from the Organization of Islamic Conference by which the Saudi Arabia called for the establishment of an impartial, sovereign, independent, bi-community Cyprus Federated State related with the Cyprus Issue as well as in much more matters how the Saudi Arabia made contributions to the issue has been tried to be explained. And again the present Study tells us how the Saudi Government rendered direct and full support to the Turkish Cypriots for their being present at the Organization of Islamic Conference as observer and that the Saudi Government is one of the few Islamic States that gave support to the issue of the Turkish Cypriots. The present Research comes to an end by summarizing the aid efforts rendered to the Turkish Cypriots in the Northern Cyprus during the King Khalid era and their reflections onto the Turkish-Saudi relationships
Reflection of the Cyprus Problem in the era of the King Khalid Bin Abdul-Aziz onto the Relations between the Republic of Turkey and Saudi Arabia 1975-1982